Pilosebaceous targeting by isotretenoin-loaded invasomal gel for the treatment of eosinophilic pustular folliculitis: optimization, efficacy and cellular analysis. (1st February 2017) - Dwivedi, Mohit; Sharma, Vijay; Pathak, Kamla
Abstract: Context: Eosinophilic pustular folliculitis is a secondary symptom associated with HIV infection appears as levels of CD4 lymphocyte cells and T4 lymphocyte cell. Isotretinoin, an analog of vitamin A (retinoid) alters the DNA transcription mechanism and interferes in the process of DNA formation. It also inhibits the eosinophilic chemotactic factors present in sebaceous lipids and in the stratum corneum of patients suffering from this ailment. Objective: The present research was aimed to formulate isotretenoin-loaded invasomal gel to deliver and target the drug to pilosebaceous follicular unit. Methods: Nine invasomal formulations (F1–F9) were prepared applying 3 2 factorial designs and characterized. Results: Formulation F9 was selected as optimized formulation due to optimum results and highest %CDP of 85.94 ± 1.86% in 8 h. Transmission electron microscopy (TEM) suggested uniformity in vesicles shape and size in F9 and developed as invasomal gel (IG). Limitations: Clinical phase-I, phase-II, and phase-III studies will be required before using on human patients. Conclusion: Confocal laser scanning microscopy (CLSM) validates that IG successfully reaches the pilosebaceous follicular unit and further studied on cell line (SZ-95) exhibited IC50 of ≤8 (25 μM of isotretenoin). Cell cycle analysis confirmed IG arrested the cell growth up to 82% with insignificant difference to pure isotretenion.